Handbook on the economics of sport - Andreff, Wladimir 1946-; Szymanski, Stefan 1960- (Edward Elgar, 2009)
This handbook presents a survey of all the major research areas in sports economics. It offers an insight into the major findings of the literature as well as researchers' views on some of the questions remaining to be answered.